2008
DOI: 10.1152/ajpregu.00863.2007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity training on muscle lactate transporters and postexercise recovery of muscle lactate and hydrogen ions in women

Abstract: Bishop D, Edge J, Thomas C, Mercier J. Effects of high-intensity training on muscle lactate transporters and postexercise recovery of muscle lactate and hydrogen ions in women. Am J Physiol Regul Integr Comp Physiol 295: R1991-R1998, 2008. First published October 1, 2008 doi:10.1152/ajpregu.00863.2007.-The purpose of this study was to investigate the effects of high-intensity interval training (3 days/wk for 5 wk), provoking large changes in muscle lactate and pH, on changes in intracellular buffer capacity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 50 publications
6
52
1
3
Order By: Relevance
“…While others have also failed to observe an increase in MCT1 and MCT4 following HIT [36] it is possible that MCT4 increased following training in the current study, resulting in improved lactate export. While we were unable to measure MCT4 this explanation seems unlikely as MCT1 and MCT4 typically change in concert [5,36]. Alternatively, the observed increases in anaerobic power may be a result of improved muscle buffering capacity.…”
Section: Mechanisms Of Increased Anaerobic Capacitycontrasting
confidence: 62%
See 1 more Smart Citation
“…While others have also failed to observe an increase in MCT1 and MCT4 following HIT [36] it is possible that MCT4 increased following training in the current study, resulting in improved lactate export. While we were unable to measure MCT4 this explanation seems unlikely as MCT1 and MCT4 typically change in concert [5,36]. Alternatively, the observed increases in anaerobic power may be a result of improved muscle buffering capacity.…”
Section: Mechanisms Of Increased Anaerobic Capacitycontrasting
confidence: 62%
“…Alternatively, the observed increases in anaerobic power may be a result of improved muscle buffering capacity. While increases in buffering capacity have been observed following HIT training [2], no changes in buffering capacity have also been reported following HIT [36]. The mechanisms underlying the increases in anaerobic power induced by the Tabata protocol, and HIT in general, remain unclear.…”
Section: Mechanisms Of Increased Anaerobic Capacitymentioning
confidence: 99%
“…This could explain the contrasting results of these studies and the present investigation. At the same time, other training studies both performed in athletes have shown that MCT1 and MCT4 remain unchanged after a period of intensified training (Clark et al 2004;Bishop et al 2008). Also, other studies have shown that the expression of MCT1 and MCT4 acutely decreased following a single bout of high-intensity exercise ).…”
Section: Discussionmentioning
confidence: 91%
“…Para ser utilizado, o lactato produzido na fibra muscular deve ser transportado para a corrente sanguínea. Para isto, uma proteína presente na membrana da célula muscular, conhecida como transportador de monocarboxilato (MCT), transporta o lactato de dentro da célula para o sangue (JUEL et al, 2004;BONEN et al, 1998;BONEN, 2000;GLADDEN, 2007;BISHOP et al, 2008). O transporte do lactato para a corrente sanguínea através dos MCTs somente é realizado em co-transporte com H + , constituindo-se, dessa forma, como um dos processos que mais contribui para a manutenção do pH intracelular (BISHOP et al, 2001;JUEL et al, 2004;THOMAS et al, 2005;GLADDEN, 2007;BISHOP et al, 2008);BOGDANIS, 2012).…”
Section: Introductionunclassified
“…Neste contexto, estudos prévios reportados na literatura objetivaram analisar a cinética de remoção de lactato frente a esforços de alta intensidade (BRET et al, 2003;MESSONNIER et al, 2006;BISHOP et al 2008;MENZIES et al, 2010). A produção de lactato indica a magnitude da capacidade de produção de ATP via metabolismo anaeróbico lático, e sua remoção para o sangue uma capacidade de regulação de pH intramuscular.…”
Section: Introductionunclassified